The Effect of Nonlinear Incentives on Performance: Evidence from “Econ 101” - Oettinger, Gerald S. (The Review of Economics and Statistics, 2002)
This paper analyzes both theoretically and empirically how an absolute grading standard that allows only a small number of distinct grades affects student course performance outcomes. The clearest prediction of the model is that course performance of “grade-motivated” students will tend to be clustered slightly above the boundaries that separate grades, as long as the variance of the random component of performance is not too large. A more tenuous prediction is that the proximity of a grade-motivated student to a grade boundary going into the final exam should influence final exam performance, after controlling for prefinal exam performance. An empirical investigation of the course performance of university students who were enrolled in introductory economics classes that used an absolute grading standard finds evidence in favor of both of these predictions. The results suggest that student effort decisions respond to the incentives created by the grading system.